Impactos do associativismo na pecuária leiteira paulista: estudo de casos. - Gerlach, Fábio Ravazi (2004)
Practice of association is the way for the small producers, that, isolated and with small production, they do not get to participate or to influence markets more and more competitive. Thus, it becomes necessary to evaluate organization`s forms that can be presented as socio-economic inclusion ways. The dissertation has for objective to impacts` evaluate of the practice of association in the economic, technological and social conditions of the milk producers. The impact evaluation was made from a set of performance indicators that allowed to evaluate the current result of the associations. The research method adopted was the case study, with multicases. The evaluation form used allowed to identify factors of success of the associations, like this as few restrictions for the development of these associative organizations. The associations are examples of success for the improvement in the life of producers, however it is a success with restrictions, therefore that this is restricted to some of the pointers and, particularly, are economic indicators. However, the social contribution of the associations for the producers is complementary and basic to the economic profits, being that these contribute excessively for the formation of the social capital. All the associations are how efficient how much to the objective to take care of its associates. One of cases, that association was disactivated, this also one revealed efficient while it was in functioning. Thus, the evaluation measure how much to the efficiency of the associations, considering that the efficiency is bigger to the measure that if they verify the indicated situations. It is distinguished in the results of that the associations that demonstrated the best ones resulted had been formed by independent and not governmental initiatives. In these conditions, these associations had contributed of more significant form for the formation of the social capital. In conclusion the work it brings two important contributions. The first is theoretician, with the presentation of a methodology for evaluation of associations of milk producers. Second it is practical, with the results of the research. The formation of the associations fortifies the producers ahead of the difficulties found in all the productive chain, since the producers if present as the link weakkest of the chain. However, this force still is restricted to the milk production, with great distance of the final and more important link of all the chain, the consumer. The practice of association is a good form of adequacy of the producing ahead to the requirements imposed for the market, but still it has very for if making. Exactly that all the good initiatives of each one of the associations were developed by all the associations, the current situation of the milk market, without politics consumption incentives, would not be enough for a significant improvement in the current picture of the milk sector.